Internal control on budget realisation reports in the food and drug control agency - Amelia, Tifa Noer; Bahalma, Lintang Arival (UiTM Cawangan Johor, 2023)
The Budget Realisation Report can also be used as a tool for stakeholders in making decisions. In order to achieve effective, transparent and accountable state financial management, internal control activities are carried out to determine the accountability value of a budget realisation report. Therefore, this research was conducted with the purpose of knowing the influence of internal control on the accountability of the Budget Realisation Report. The sample used was 30 people in the financial sector office at the Deputy for Processed Food Production Supervision of Indonesia. The data used is quantitative data in the form of primary data sources directly from respondents through questionnaires. The analytical techniques used in this study include: 1) Descriptive Statistical Test; 2) Classical Assumption Test; and 3) Multiple Linear Regression. This paper shows that internal control has significant impact on budget realisation report accountability. The significant of the result is to prove that physical internal control is not working without IT internal control.